A Correlation between EFL Students’ Vocabulary Knowledge and Reading Comprehension Ability - Taladngoen, Unaree; Thong-ngamkham, Tonghathai; Palawatwichai, Naruporn; Kaewseesuk, Sirithon (Manutsat Paritat: Journal of Humanities, 2022)
The present study aimed to examine the vocabulary knowledge of the first-year undergraduate students at Rajamangala University of Technology Lanna (RMUTL) Phitsanulok and the correlation between the students’ vocabulary knowledge and reading comprehension ability. The participants were 49 first-year undergraduate students at RMUTL Phitsanulok, who enrolled in a foundation English course entitled GEBLC 102 English for Life Skills. The research instruments were the Vocabulary Level Tests and the researcher-constructed reading comprehension test. Descriptive statistics were employed for data analyses. Pearson’s correlation coefficient was used to find the correlation between the students’ vocabulary knowledge and reading comprehension ability. The results revealed that the participants did not have sufficient vocabulary knowledge as expected. A correlation between the two variables was also statistically significant at the 0.05 level. EFL teachers are suggested to implement various methods to enhance newly-enrolled undergraduate students’ vocabulary knowledge and reading comprehension, such as organization of a vocabulary-based and reading-based preparatory course at the beginning of the semester and implementation of extensive reading throughout the academic year.